KEDUDUKAN HAK RETENSI BENDA GADAI OLEH PT. PEGADAIAN DALAM HAL DEBITUR WANPRESTASI - Gusti Pati Runtung, Mauritius; Parwata, I Gusti Ngurah (Kertha Semaya : Journal Ilmu Hukum, 2013)
This research aims to know the rights of retention of pawn object by PT Pegadaianin case the debtor defaults, while the approach is conducted legally, i.e. normative researchmethod with guided the legislation. Retention rights are rights that provide security withhis master before a debt repaid. In the pledge of rights of retention which are owned by thelender or mortgage recipients is used in executing the debtor's collateral or pledge giverthat is by conducting an auction. The auction was conducted due to the debtor or creditorparty givers pledge suffered defaults. The results showed PT. Pegadaian as the borrower orrecipient of a pawn has the authority or right to make the execution directly against objectsthat are to be guaranteed in case of debtor default or pawn giver.
Keywords: Rights Of Retention, Pledge, Defaults